2020
DOI: 10.22434/ifamr2019.0165
|View full text |Cite
|
Sign up to set email alerts
|

Digital integration to enhance market efficiency and inclusion of smallholder farmers: a proposed model for fresh fruit and vegetable supply chain

Abstract: High-value agriculture in India is witnessing a transformation, specifically in fresh fruits and vegetables (FFV). Supply chain stakeholders, mainly small and marginal farmers, receive a very minimal share in consumer rupee due to market uncertainty, high post-harvest losses, information asymmetry, lack of processing facilities and the erratic demand-supply situation. The current study draws from an extensive review to propose a competitive, inclusive, sustainable and scalable supply chain model of primary pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Other two agtechs (A2 and A3) help producers with an emphasis on vegetable production to more easily find their final consumers, creating solutions for the consumption link of the agribusiness chain. According to Nedumaran et al. (2020), market integration platforms guarantee the producer–consumer connection, increase price transparency and reduce the role of the intermediary and the handling of products at different points.…”
Section: Resultsmentioning
confidence: 99%
“…Other two agtechs (A2 and A3) help producers with an emphasis on vegetable production to more easily find their final consumers, creating solutions for the consumption link of the agribusiness chain. According to Nedumaran et al. (2020), market integration platforms guarantee the producer–consumer connection, increase price transparency and reduce the role of the intermediary and the handling of products at different points.…”
Section: Resultsmentioning
confidence: 99%
“…Digital platforms should offer information and services relevant to agriculture, including weather forecasts, market prices, and farming techniques. Moreover, Access to digital marketplaces can help farmers connect with buyers and access a broader market for their products [27,28]. Nonetheless, government policies that support digital inclusion, such as subsidies for digital devices or tax incentives for telecom companies, can be critical, especially for smallholder farmers.…”
Section: The Imperative Of Digital Inclusion For Smallholder Farmersmentioning
confidence: 99%
“…The results of the economic analysis conducted within the context of this study revealed that free consignment and minimum guaranteed arrangements were preferred by the exporters of Chilean apples when they exported to a country with a safe business environment. Nedumaran et al [50] proposed an SC model to connect farmers directly and efficiently with customers. The model also has as an aim to reduce postharvest losses.…”
Section: Value Chain Indicators Of Ffvscsmentioning
confidence: 99%